2017
DOI: 10.1007/s12282-017-0773-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Syndecan-1 levels in the sera of patients with breast cancer correlate with tumor size

Abstract: The positive correlation between soluble Syndecan-1 levels and tumor size in the present study highlights the importance of different varieties (cell-bound and soluble) of this molecule in the breast tumor progression and their significance as tumor biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The altered expression profiles of ECM components, such as integrins, cadherins, and syndecans, have been found to correlate with tumorigenesis, tissue invasiveness, metastatic behavior, and survival in many types of cancer, including breast cancer [25,26]. Breast cancer presents the highest incidence of all tumors and is still the first cause of death from cancer in women.…”
Section: Introductionmentioning
confidence: 99%
“…The altered expression profiles of ECM components, such as integrins, cadherins, and syndecans, have been found to correlate with tumorigenesis, tissue invasiveness, metastatic behavior, and survival in many types of cancer, including breast cancer [25,26]. Breast cancer presents the highest incidence of all tumors and is still the first cause of death from cancer in women.…”
Section: Introductionmentioning
confidence: 99%
“…HPSE expression strongly correlates with poor survival in BC (Sun et al, 2017) and serum levels of shed SDC1 have been identified to be informative in regards to progression of several cancers including breast (Joensuu et al, 2002;Vassilakopoulos et al, 2005;Szarvas et al, 2016). Shed SDC1 abundance detected in serum has been associated with BC size (Malek-Hosseini et al, 2017), and to be a result of chemotherapy (Ramani and Sanderson, 2014). SDC1 gene expression in BC can be prognostic (Cui et al, 2017), with its induction in stromal fibroblasts identified in invasive BC (Yang et al, 2011;Vlodavsky et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…63,70 The MMP-9-mediated shedding of syndecan-1 and -4 by HeLa cells involves ECM degradation during cancer cell metastasis and invasion, and shed syndecan-1 is involved in tumor cell proliferation. 68 A positive correlation between shed syndecan-1 levels and tumor size was reported in breast tumor progression, 71 and shed syndecan-1 was shown to bind activated vascular endothelial growth factor receptor 2 (VEGFR2) and thereby stimulate tumor cell invasion, 72 suggesting that it is involved in tumor angiogenesis. Heparanase-1, which is upregulated in many human tumors in association with increases in the metastatic potential of tumor cells, regulates syndecan-1 expression and shedding to influence breast cancer progression.…”
Section: Syndecan Shedding and Ecm Remodeling In Cancer Cellsmentioning
confidence: 99%